Theoretical Study of the Effective Parameters for Direct Contact Membrane Distillation in Hollow Fiber Modules - Salah S. Ibrahim (Engineering and Technology Journal, 2014)
The main object of this research is to study the parameters that have important effects upon performance of the direct contact membrane distillation (DCMD) process, through predicting the effects of the outside and inside diameters, the thickness of the hollow fiber membrane, the pore size, porosity, tortuosity, module length, number of fibers in module, inlet feed temperature, inlet feed concentration, inlet permeate temperature and the velocity of feed and permeate. The effective parameters that influence the performance of DCMD are classified into membrane characteristics, operating conditions, and parameters of module specifications. This study is based on an experimental system of Wang et al., 2008 [1] as typical system.It was found that theincreaseof the permeate fluxis by selecting an optimum thickness for each inside or outside diameter of hollow fibers and anoptimum number of fibers in the module and increasing the porosity and pore size within practical range and decreasing of tortusity andas well as increasing the inlet feed temperature rather than decreasing the inlet permeate temperature for constant temperature difference between feed and permeate. Also it is found that the feed concentration and fiber length play an inverse role with the permeate flux.